1988
DOI: 10.1161/01.res.63.3.628
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabeled acetate as a tracer of myocardial tricarboxylic acid cycle flux.

Abstract: The kinetics of [1-14C]acetate oxidation in isolated perfused rat hearts have been determined over a range of perfusion conditions. Effluent measurements demonstrated that 14CO2 cleared biexponentially over 50 minutes after bolus injection of [1-14C]acetate into normoxic hearts perfused with 5 mM glucose and 10 mU/ml insulin. The clearance half-time (t1/2) for the predominant initial clearance phase was 3.1 +/- 0.5 minutes (n = 4). MVO2 was varied over a fourfold range by hypoxia and phenylephrine stimulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(55 citation statements)
references
References 24 publications
4
51
0
Order By: Relevance
“…Based on this hypothesis and using the previously determined citrate concentration (1.48 μmol/g dry weight) [49], V TCA was estimated to be 6.7 ± 1.7 μmol · g − 1 · min − 1 (dry weight). Although this value is comparable to previously published fluxes determined from 13 C MRS or radioactive labeled carbon experiments performed during a long acetate infusion in perfused heart or in vivo and typically leading to V TCA comprised between 7.4 and 14 μmol · g −1 · min −1 (dry weight) [3,15,16,61], the values estimated in the present work correspond to the lower end of the range. This might at first appear counter-intuitive since the RPP recorded in this in vivo study (~50 k mm Hg min −1 ; Table 1) was significantly larger than the reported RPP in earlier studies (~20 k to 30 k mm Hg min − 1 ) [3,15], and a larger V TCA is usually expected with increased RPP.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Based on this hypothesis and using the previously determined citrate concentration (1.48 μmol/g dry weight) [49], V TCA was estimated to be 6.7 ± 1.7 μmol · g − 1 · min − 1 (dry weight). Although this value is comparable to previously published fluxes determined from 13 C MRS or radioactive labeled carbon experiments performed during a long acetate infusion in perfused heart or in vivo and typically leading to V TCA comprised between 7.4 and 14 μmol · g −1 · min −1 (dry weight) [3,15,16,61], the values estimated in the present work correspond to the lower end of the range. This might at first appear counter-intuitive since the RPP recorded in this in vivo study (~50 k mm Hg min −1 ; Table 1) was significantly larger than the reported RPP in earlier studies (~20 k to 30 k mm Hg min − 1 ) [3,15], and a larger V TCA is usually expected with increased RPP.…”
Section: Discussionsupporting
confidence: 88%
“…Although reporting similar V TCA , the obtained MVO 2 varied between 16 (in vivo [15]) and 29 to 31 μmol · g −1 · min − 1 (dry weight) (in perfused heart [3,16,61]), suggesting a more efficient energy conversion in vivo. Future studies should incorporate such a comparison to validate the estimated values of V TCA obtained in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…3 There was a close correlation between the slope of the rapid clearance phase and the tricarboxylic acid (TCA) cycle flux under varying work load conditions. In contrast to results with labeled palmitate, changes in substrate supply did not alter the tissue kinetics of [1-1'4C]acetate except after administration of acetate in nontracer amounts, equivalent to nonphysiologically high acetate serum levels.…”
Section: Armbrecht [L-'c]acetate As a Tracer For Mvo2 1595mentioning
confidence: 98%
“…39 The early rapid clearance of acetate correlates closely with myocardial oxygen consumption, and the relationship of myocardial 11 C-labeled acetate kinetics to cardiac work offers a noninvasive parameter for cardiac efficiency that can be used to demonstrate the effect of pharmacological and pacing interventions on cardiac energetics. 40,41 Fluorine 18-labled fluorodeoxyglucose ( 18 F-FDG) traces cellular glucose uptake and phosphorylation and can be used to quantify regional glucose metabolism.…”
Section: Metabolism (Pet/mr Spectroscopy)mentioning
confidence: 99%